2021
DOI: 10.3389/fped.2020.575741
|View full text |Cite
|
Sign up to set email alerts
|

Is Testicular Torsion a Real Problem in Pediatric Patients With Cryptorchidism?

Abstract: Purpose: To present management and outcomes of patients with cryptorchidism suffering from testicular torsion.Methods: This is a retrospective review of pediatric patients with torsion of undescended testes, who were treated between 2009 and 2019. We recorded: the age, symptoms, duration of torsion, results of physical examination, surgery findings, and additional treatment. Additionally, an extensive online literature search, from 2015–2020, was performed to identify other similar case series.Results: We iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…[ 17 ] In children presenting with abdominal groin pain and empty ipsilateral scrotum, torsion of undescended testis should be considered. [ 18 ] Torsion of cryptorchidism is accounted for about 5% in all testicular torsion cases, [ 19 ] and the incidence of torsion of cryptorchidism appears to be higher than torsion of normally descended testis. [ 20 , 21 ] Physical examination is crucial in diagnosing testicular torsion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 17 ] In children presenting with abdominal groin pain and empty ipsilateral scrotum, torsion of undescended testis should be considered. [ 18 ] Torsion of cryptorchidism is accounted for about 5% in all testicular torsion cases, [ 19 ] and the incidence of torsion of cryptorchidism appears to be higher than torsion of normally descended testis. [ 20 , 21 ] Physical examination is crucial in diagnosing testicular torsion.…”
Section: Discussionmentioning
confidence: 99%
“…About 40% of boy undergoing surgery for testicular torsion performed orchiectomy, [ 3 ] and rate of orchiectomy is higher in torsion of cryptorchidism than in torsion of descended testis. [ 19 , 29 ] Another study revealed poor rates of surgical salvage in torsion of cryptorchidism. [ 30 ] It was because the atypical presentations made parents underestimate the children’s condition.…”
Section: Discussionmentioning
confidence: 99%
“…These patients required a high index of suspicion of TT, and then an urgent ultrasound scan was performed. Moreover, about 5% of patients who presented with torsion suffered from cryptorchidism, which may be explained by incorrect spasm or contraction of cremasteric muscle ( 21 , 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Testicular torsion of cryptorchidism can occur at all ages ( 5 ). Cases of cryptorchid testicular torsion have been reported in patients ranging in age from 16 days to 14 years ( 6 , 12 , 13 ). In our study, the age of onset was mostly before puberty, specifically during infancy and early childhood.…”
Section: Discussionmentioning
confidence: 99%